2020
DOI: 10.3389/fncel.2020.590960
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Neural Stem Cell Secretome for Regenerative Neuroimmunology

Abstract: Increasing evidence foresees the secretome of neural stem cells (NSCs) to confer superimposable beneficial properties as exogenous NSC transplants in experimental treatments of traumas and diseases of the central nervous system (CNS). Naturally produced secretome biologics include membrane-free signaling molecules and extracellular membrane vesicles (EVs) capable of regulating broad functional responses. The development of high-throughput screening pipelines for the identification and validation of NSC secreto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 108 publications
(139 reference statements)
1
24
0
2
Order By: Relevance
“…The influence on NSC fate, however, may differ depending on the regional origin or the specific developmental state of the NSCs 12,13 . In addition to their impact on neurogenesis, NSC‐EVs exhibit immunomodulatory activity turning them to promising candidates for application in regenerative therapies of brain disease or injuries 14,15 …”
Section: Cellular Routes Of Neural Evsmentioning
confidence: 99%
“…The influence on NSC fate, however, may differ depending on the regional origin or the specific developmental state of the NSCs 12,13 . In addition to their impact on neurogenesis, NSC‐EVs exhibit immunomodulatory activity turning them to promising candidates for application in regenerative therapies of brain disease or injuries 14,15 …”
Section: Cellular Routes Of Neural Evsmentioning
confidence: 99%
“…Studies have shown that the source of these vesicle correlated well with the expression of specific surface antigens [ 235 237 ]. Furthermore, several studies have demonstrated that sEVs generated by NSCs had therapeutic efficiency against ischemic, inflammatory, and neurodegenerative diseases [ 238 , 239 ].…”
Section: Cell Transplantation and Spinal Cord Repairmentioning
confidence: 99%
“…Recently, the paradigm of regenerative effects of NSCs/NPCs has shifted from the concept of «cell replacement» (remodeling) to the concept of «functional or therapeutic plasticity» (modulation of the microenvironment). This is based on a wide range of regulatory paracrine effects of these cells, so called «bystander effects», that provide neuroprotection, modulation of inflammation and immune response and help to repair damaged neural tissue [10][11][12][13]. In this regard, much attention is paid to the study of factors produced by NSCs/ NPCs and thus enrich the culture media during cultivation as a released molecules or as a extracellular vesicles: neurotrophic, growth factors, morphogens, immunomodulatory cytokines (NGF, BDNF, NT-3, GDNF, TGF-β1, TGF-β2, VEGF, IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ TNF-α), chemokines (CXCL12), prostaglandins (PGE2), microRNAs, etc.…”
mentioning
confidence: 99%
“…In this regard, much attention is paid to the study of factors produced by NSCs/ NPCs and thus enrich the culture media during cultivation as a released molecules or as a extracellular vesicles: neurotrophic, growth factors, morphogens, immunomodulatory cytokines (NGF, BDNF, NT-3, GDNF, TGF-β1, TGF-β2, VEGF, IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ TNF-α), chemokines (CXCL12), prostaglandins (PGE2), microRNAs, etc. [10][11][12][13][14][15][16][17][18][19]. These secreted factors or NSCs/NPCs secretome [11,20] are the mediators of bystander-effects, able to regulate a wide range of processes at the cellular, tissue, organ and systemic levels and are considered a key component of these regulatory mechanisms [12,[21][22][23].…”
mentioning
confidence: 99%
See 1 more Smart Citation